MAKESPAN MINIMIZATION IN BATIK MURNI SMEs WITH PALMER, CAMPBELL DUKDEK SMITH, AND HEURISTIC POUR ALGORITHM - Wildanul Isnaini; Emylia Arghawaty; Zahrul Ashari (Spektrum Industri, 2020)
Batik Murni is one of the Small and Medium Enterprises (SMEs) in Madiun Region that produces batik tulis and batik cap. However, the production of Batik Murni has not applied the exact method in production scheduling. This SMEs still uses intuition to make the production schedule. This condition can give disadventages for the SMEs, overstock and stockout will be happened. In this study, the researcher wants to offer a solution for the scheduling problems so Batik Murni can increase theri productivity performance. Researchers offer three production scheduling methods aimed at minimizing the makespan of Batik Tulis. The three methods used are Palmer, Champbell Dukdek Smith (CDS), and Heuristic Pour Algorithm. From this research, It can be concluded that the best production scheduling optimization at Batik Murni SMEs is obtained from the Palmer method. With makespan of 4837 minutes or 11 working days so the makespan can be minimized 54,2%.Â  In the order of the production process is batik sejuta bunga â€“ batik batik turi tabur - batik seger arum - batik pecel.